Ibn Khaldûn’s Perspective About Equilibrium of Price in Muqaddimah Book - Khoirunnisa’, Siti (Jurisdictie: Jurnal Hukum dan Syariah, 2015)
The purpose of the research was to understand about Ibn Khaldûn’s perspective about equilibrium of price in his era and about the factors which influence equilibrium of price and to know about the similarities and the differences between Ibn Khaldûn’s equilibrium of price and contemporary equilibrium of price. This research was Qualitative research. The approach used in this research was conceptual approach. It was studying about social phenomenon which has been happen in Ibn Khaldûn’s era within use the concept of him in muqaddimah book. From this research could be seen that the equilibrium of price depends on Ibn Khaldûn’s perspective will be happen when the quantity of demand as same as the quantity of supply of goods. It is related to the available of goods, and the situation of development of city. It also become the concept in the economic modern when the supply and demand of product should influence to the equilibrium of price. And there were some factors influenced the equilibrium of price in his era. The capability of workers and the needed of employer, the condition of city and the population there, the additional cost of goods because of taxation, etc. Tujuan dari penelitian ini adalah untuk memahami tentang perspektif Ibn Khaldun tentang keseimbangan harga di jamannya dan tentang faktor-faktor yang mempengaruhi keseimbangan harga dan mengetahui tentang persamaan dan perbedaan antara ekuilibrium Ibn Khaldun harga dan keseimbangan kontemporer harga. Penelitian ini merupakan penelitian kualitatif. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan konseptual. Sedang mempelajari tentang fenomena sosial yang telah terjadi di era Ibn Khaldun dalam penggunaan konsep dirinya dalam buku Muqaddimah. Dari penelitian ini dapat dilihat bahwa keseimbangan harga tergantung pada perspektif Ibn Khaldun akan terjadi ketika jumlah permintaan sebagai sama dengan kuantitas pasokan barang. Hal ini terkait dengan tersedia barang, dan situasi dari perkembangan kota. Hal ini juga menjadi konsep dalam ekonomi modern ketika pasokan dan permintaan produk harus berpengaruh terhadap keseimbangan harga. Dan ada beberapa faktor yang mempengaruhi keseimbangan harga di jamannya. Kemampuan pekerja dan diperlukan dari majikan, kondisi kota dan penduduk di sana, biaya tambahan barang karena perpajakan, dll